2004
DOI: 10.1017/s0031182004005190
|View full text |Cite
|
Sign up to set email alerts
|

Babesiosis of cattle

Abstract: Tick fever or cattle fever (babesiosis) is economically the most important arthropod-borne disease of cattle worldwide with vast areas of Australia, Africa, South and Central America and the United States continuously under threat. Tick fever was the first disease for which transmission by an arthropod to a mammal was implicated at the turn of the twentieth century and is the first disease to be eradicated from a continent (North America). This review describes the biology of Babesia spp. in the host and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
604
0
27

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(694 citation statements)
references
References 134 publications
12
604
0
27
Order By: Relevance
“…This is may be due to higher concentration of the former parasite in the capillary and veins than the latter parasite which evenly distributed in the whole blood vasculature. Previous studies have also indicated that cattle infected with B. bovis remain carriers for long periods, while those infected with B. bigemina remain carriers for only a few months [28].…”
Section: Discussionmentioning
confidence: 98%
“…This is may be due to higher concentration of the former parasite in the capillary and veins than the latter parasite which evenly distributed in the whole blood vasculature. Previous studies have also indicated that cattle infected with B. bovis remain carriers for long periods, while those infected with B. bigemina remain carriers for only a few months [28].…”
Section: Discussionmentioning
confidence: 98%
“…B. bigemina is protozoa of major concern in Indian cattle herds, parasitizing both cattle and buffaloes (Muraleedharan et al 1984). Further, buffaloes might serve as reservoirs for the infections of cattle, since they are together in the dairy farms and continue to infect the tick vector (Bock et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The parasite is transmitted transovarially by the larval stages of Rhipicephalus (Boophilus) microplus ticks (Chauvin et al 2009). Losses due to babesiosis to the livestock industry are enormous and are incurred from mortality, ill-thrift, loss of milk/meat production, draft power, cost on control measures, and also through its impact on international cattle trade (Bock et al 2004). India suffers losses of about 57.2 million US dollars annually due to impact of babesiosis and anaplasmosis on livestock and its control (McLeod and Kristjanson 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Such is the case with bovine babesiosis in the border region of Mé xico and the USA. Bovine babesiosis is a common and widely distributed arthropod-transmitted disease (Homer et al, 2000) and is considered the most economically important disease of livestock (Bock et al, 2004). The disease is caused by the protozoan parasites Babesia bigemina and Babesia bovis, transmitted to the host by the tick vectors Rhipicephalus annulatus and Rhipicephalus microplus (Bock et al, 2004), known as cattle fever ticks (CFTs).…”
mentioning
confidence: 99%
“…Bovine babesiosis is a common and widely distributed arthropod-transmitted disease (Homer et al, 2000) and is considered the most economically important disease of livestock (Bock et al, 2004). The disease is caused by the protozoan parasites Babesia bigemina and Babesia bovis, transmitted to the host by the tick vectors Rhipicephalus annulatus and Rhipicephalus microplus (Bock et al, 2004), known as cattle fever ticks (CFTs). Although cattle are the main host for CFTs, other ungulates such as white-tailed deer (Odocoileus virginianus; Hagan and Bruner, 1951;Cantú et al, 2007), sheep (Ovis aries; Mungall and Sheffield, 1994), and nilgai antelope (Boselaphus tragocamelus; Sheffield et al, 1983) have been found with CFTs.…”
mentioning
confidence: 99%